Robust Four-Wave Mixing and Double Second-Order Optomechanically Induced Transparency Sideband in a Hybrid Optomechanical System - Huajun Chen (Photonics, 2021)
We theoretically research the four-wave mixing (FWM) and second-order sideband generation (SSG) in a hybrid optomechanical system under the condition of pump on-resonance and pump off-resonance, where an optomechanical resonator is coupled to another nanomechanical resonator (NR) via Coulomb interaction. Using the standard quantum optics method and input–output theory, we obtain the analytical solution of the FWM and SSG with strict derivation. According to the numerical simulations, we find that the FWM can be controlled via regulating the coupling strength and the frequency difference of the two NRs under different detuning, which also gives a means to determine the coupling strength of the two NRs. Furthermore, the SSG is sensitive to the detuning, which shows double second-order optomechanically induced transparency (OMIT) sidebands via controlling the coupling strength and frequencies of the resonators. Our investigation may increase the comprehension of nonlinear phenomena in hybrid optomechanics systems.